A swelling tape and preparation method thereof
By adopting a three-layer structure swelling tape, using porous polyimide base layer and swelling layer raw material liquid of different viscosity, the problem of dissolution or brittle cracking of existing swelling tape in high temperature environments is solved, and the effect of maintaining effective tightening in lithium batteries for a long time is achieved.
Patent Information
- Application Number
- CN202411543504.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-10-31
AI Technical Summary
The existing swelling tape is prone to dissolve or brittle under the high temperature environment of lithium batteries, resulting in the inability to maintain effective tightening of the battery cell for a long time, affecting the safety performance of the battery.
The swelling tape with a three-layer structure is adopted, including a swelling layer, a base material layer and a hot melt adhesive layer stacked in sequence. The viscosity of the raw material liquid of the first swelling layer is smaller than that of the raw material liquid of the second swelling layer. The first swelling layer part is arranged in the pores of the porous polyimide substrate layer to enhance the interlayer connection strength.
The swelling tape of this structure has good swelling performance in lithium battery electrolyte, and remains intact during long-term use at high temperatures, insoluble, non-brittle cracks, and good mechanical properties, effectively solving the problems of the short service life of existing swelling tape at high temperatures.
Smart Images

Figure CN119161813B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of adhesive materials, and in particular relates to a swelling tape and a preparation method thereof. Background Art
[0002] Lithium-ion batteries have the advantages of high energy density and power density, high operating voltage, light weight, small size, long cycle life, good safety, and green environmental protection. They are widely used in portable appliances, power tools, large-scale energy storage, electric transportation power supply, etc. Lithium-ion batteries mainly include cylindrical, soft-pack and square batteries. Among them, cylindrical batteries have higher production efficiency and lower production cost, mature process technology, and low PACK cost. They have been more widely used in the fields of new energy vehicles, energy storage and power tools. With the development of battery technology, the cylindrical lithium battery has become larger and larger, and its energy density is getting higher and higher, which also requires higher safety performance of the battery. During the use of cylindrical batteries, due to frequent shaking and vibration, and during the production, transportation and assembly of batteries into modules, they will inevitably be hit, which can easily cause a gap between the battery cell and the outer shell, resulting in relative movement, resulting in electrode damage, battery short circuit and other problems, which greatly affects the use of the battery.
[0003] Based on the above problems, the commonly used solution is to stick a swelling tape on the surface of the battery cell. When the tape contacts the electrolyte, it will swell and fill the entire gap, thereby fixing the battery cell and resisting external impact. For example, CN104798223A discloses a swelling tape for filling the gap. A thermoplastic polyurethane (TPU) with a thickness of about 40 μm is selected as the base layer, and an acrylic pressure-sensitive adhesive is used as the adhesive layer to prepare a swelling tape. It swells into a three-dimensional shape in a carbonate electrolyte, can effectively fill the gap between the electrode assembly and the inner wall of the shell, and fix the electrode assembly, thereby improving the safety performance of the battery. CN113072889A discloses a thick swelling tape for cylindrical batteries and its preparation method, wherein polyvinyl acetate (PVAC), SBS, amino resin curing agent, and organic acid catalyst are prepared into a mixed solution, and a 30-50 μm film is prepared by coating, drying and curing, and then compounded with a pressure-sensitive adhesive to prepare a swelling tape, and the tape can fill the gap between the battery core of the cylindrical battery and the cylindrical shell in all directions after swelling in the electrolyte, thereby effectively fixing the battery core of the cylindrical battery and the cylindrical shell. CN1992393B discloses a lithium-ion secondary battery, in which a sealing tape attached to the outer periphery of the electrode assembly to prevent the winding electrode assembly from being unwound is formed by a material having an affinity for the electrolyte, including a polymer material containing an ester group or a carboxyl group, a polymer in the group of polyvinyl difluoride, polybutadiene and polyisoprene, and is used to absorb the electrolyte and swell, so that the electrode assembly and the tank are attached to each other, thereby preventing the welding part of the electrode terminal from being disconnected due to the rotation or floating of the electrode assembly. CN219123264U discloses a lithium-ion battery, wherein a first insulating protective layer is provided on the surface of the cut empty foil area of the current collector, and a second insulating protective layer is provided on the outer surface of the first insulating protective layer, and the second insulating protective layer can swell in the length and width directions under the action of the electrolyte, and finally cover the cut edge of the current collector, which can completely prevent the cutting burrs from piercing the diaphragm. CN220283958U discloses a swelling tape, wherein a first adhesive layer and a second adhesive layer are respectively provided on both sides of the swelling layer, and the first adhesive layer and the second adhesive layer play the role of fixing the battery, and holes are punched in the first adhesive layer and the second adhesive layer to form a first channel and a second channel respectively, so that the electrolyte flows into the swelling layer, and the swelling layer expands under the immersion of the electrolyte, thereby increasing the binding between the swelling tape and the bare battery and the shell, which helps to improve the passing rate of the cylindrical battery through the drop roller, etc., thereby improving the battery safety performance.
[0004] The above-mentioned swelling tape has a certain swelling property in the electrolyte, and can achieve the fixation of the battery cell and the cylindrical shell. However, the battery will generate high temperature inside during use. Under long-term high temperature conditions in the organic electrolyte of the lithium battery, the adhesive layer and the swelling layer of the swelling tape are easily dissolved or the swelling layer is broken, resulting in the inability to maintain effective fastening of the battery cell for a long time. There is also a three-layer structure with a porous support layer in the middle to solve the mechanical strength problem of the swelling tape, but due to the different expansion coefficients of each layer, the simple multi-layer hot-pressed laminated structure has poor stability. When used for a long time in a high-temperature electrolyte environment, there is still a problem of separation of the swelling layer, the support layer and the adhesive layer, resulting in the failure of the swelling tape. Based on this, it is necessary to provide a new swelling tape that has both good swelling properties and excellent dissolution resistance to solve the above problems. Summary of the invention
[0005] The present invention aims to overcome the problems in the prior art and provides a swelling tape and a preparation method thereof. The swelling tape comprises a swelling layer, a substrate layer and a hot-melt adhesive layer which are stacked in sequence, wherein the swelling layer is composed of a two-layer structure, the viscosity of the raw material liquid of the first swelling layer is less than the viscosity of the raw material liquid of the second swelling layer; the substrate layer is a porous polyimide substrate layer, and the first swelling layer is at least partially arranged in the holes of the substrate layer. Through the arrangement of the above structure, the connection strength between the swelling layer and the substrate layer is greatly improved. At the same time, the swelling tape of this structure has good swelling performance in lithium battery electrolyte, and when used for a long time at high temperature, the tape does not dissolve or crack, and the layers remain intact and do not delaminate and fall off, and the mechanical properties are maintained well, which effectively solves the problems of the existing swelling tape being easy to dissolve at high temperature for a long time and having a short service life.
[0006] To achieve the above-mentioned object of the present invention, the first aspect of the present invention provides a swelling tape, which comprises a swelling layer, a substrate layer and a hot melt adhesive layer stacked in sequence, wherein the swelling layer is composed of two layers stacked, wherein the first swelling layer is close to the substrate layer, and the second swelling layer is above the first swelling layer and away from the substrate layer;
[0007] The viscosity of the raw material liquid of the first swelling layer is less than the viscosity of the raw material liquid of the second swelling layer;
[0008] The substrate layer is a porous polyimide substrate layer;
[0009] The first swelling layer is at least partially disposed in the pores of the substrate layer;
[0010] As a preferred technical solution, 30% to 50% of the first swelling layer is disposed in the pores of the substrate layer;
[0011] As a preferred technical solution, the thickness of the first swelling layer located on the surface of the substrate layer is 1-2 μm; the thickness of the second swelling layer is 2-4 μm.
[0012] As a preferred technical solution, the porous polyimide substrate layer has a thickness of 10-20 μm; as a further preferred technical solution, the porous polyimide substrate layer.
[0013] As a preferred technical solution, the porosity of the porous polyimide substrate is 40-80%, and the pores in the substrate are randomly distributed and do not penetrate the substrate from top to bottom.
[0014] As a preferred technical solution, the raw materials of the first swelling layer are, in parts by mass:
[0015] 20-30 parts of polytrimethylene carbonate;
[0016] 20-30 parts of polypropylene glycol malonate;
[0017] 1~5 parts of curing agent;
[0018] Catalyst 0~1 part;
[0019] 100-150 parts of solvent;
[0020] As a preferred technical solution, the raw materials of the second swelling layer are, by weight:
[0021] 40-70 parts of polytrimethylene carbonate;
[0022] 40-70 parts of polybutylene succinate;
[0023] 5~12 parts of curing agent;
[0024] Catalyst 0~1.5 parts;
[0025] 150~250 parts of solvent.
[0026] As a preferred technical solution, in the raw materials of the first swelling layer and the second swelling layer, the solvents are independently selected from N,N-dimethylformamide or ethyl acetate.
[0027] As a preferred technical solution, the molecular weights of the polytrimethylene carbonate, polypropylene malonate, and polybutylene succinate are all 80,000-180,000. If the molecular weight is too high, it cannot be dissolved in the solvent, and the volume swelling effect of the swelling tape in the electrolyte cannot be guaranteed; if the molecular weight is too low, even through curing and cross-linking, the resulting swelling tape is easily dissolved by the electrolyte, and the swelling result cannot meet the requirements. In order to better achieve the combination of the first swelling layer and the substrate layer, the molecular weights of the polytrimethylene carbonate and polypropylene malonate in the raw materials for the first swelling layer are smaller than the molecular weights of the polytrimethylene carbonate and polybutylene succinate in the raw materials for the second swelling layer.
[0028] As a preferred technical solution, in the raw materials of the first swelling layer and the second swelling layer, the curing agent is independently selected from isocyanate accumulation curing agents such as toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), hexamethylene diisocyanate (HDI) or amino resin curing agents such as aliphatic amines, aromatic amines, and cyclic amines, and the curing agent can achieve the curing and crosslinking of polytrimethylene carbonate and polybutylene succinate or polytrimethylene carbonate and polypropylene malonate.
[0029] As a preferred technical solution, the amount and selection of the catalyst depends on the selection of the curing agent. When an isocyanate curing agent is selected, no catalyst is needed; when an amino resin curing agent is selected, the catalyst is p-toluenesulfonic acid.
[0030] The second aspect of the present invention provides a method for preparing a swelling tape, which specifically comprises the following steps:
[0031] (1) Preparation of the first swelling layer raw material solution:
[0032] (1.1) Weighing polytrimethylene carbonate, polypropylene glycol malonate, a curing agent, a catalyst and a solvent according to the mass parts of the raw materials of the first swelling adhesive layer, and dissolving polytrimethylene carbonate and polypropylene glycol malonate with 4 / 5 of the solvent to obtain a solution 1;
[0033] (1.2) diluting the curing agent and catalyst with 1 / 5 of the solvent to obtain solution 2,
[0034] (1.3) adding the solution 2 to the solution 1, stirring evenly and filtering to obtain the first swelling layer raw material solution;
[0035] (2) Preparation of the second swelling layer raw material solution:
[0036] (2.1) Weighing polytrimethylene carbonate, polybutylene succinate, a curing agent, a catalyst and a solvent according to the mass parts of the raw materials for the second swelling adhesive layer, and dissolving polytrimethylene carbonate and polybutylene succinate with 4 / 5 of the solvent to obtain a solution 3;
[0037] (2.2) diluting the curing agent and catalyst with 1 / 5 of the solvent to obtain solution 4,
[0038] (2.3) adding the solution 4 to the solution 3, stirring evenly and filtering to obtain the second swelling layer raw material solution;
[0039] (3) applying the first swelling layer raw material liquid to the surface of the substrate layer, and obtaining the first swelling layer after curing and drying, and then applying the second swelling layer raw material liquid to the surface of the first swelling layer away from the substrate layer, and obtaining the second swelling layer after curing and drying;
[0040] (4) applying the hot melt adhesive liquid onto the release surface of the release film, and obtaining a hot melt adhesive layer after curing and drying;
[0041] (5) The surface of the base layer stacked with the first swelling layer and the second swelling layer obtained in step (3) away from the first swelling layer is attached to the surface of the hot melt adhesive layer obtained in step (4) away from the release film and hot-pressed and laminated, and the swelling tape is obtained after removing the release film.
[0042] As a preferred technical solution, the coating and drying conditions of the first swelling layer raw material liquid in step (3) are: the coating speed is 10-12 m / min, and the raw material liquid enters the oven at this speed for curing and drying, the oven has 8 sections, and the temperatures of sections 1-8 are 90°C, 100°C, 110°C, 120°C, 130°C, 120°C, 110°C, and 90°C respectively. The coating and drying conditions of the second swelling layer raw material liquid are: the coating speed is 8-10 m / min, and the raw material liquid enters the oven at this speed for curing and drying, the oven has 8 sections, and the temperatures of sections 1-8 are 90°C, 100°C, 115°C, 125°C, 140°C, 155°C, 110°C, and 90°C respectively.
[0043] If the coating speed of the two swelling layers is too slow and the efficiency is low, the resin in the swelling layer will be excessively cross-linked. If the coating speed is too fast, the solvent may not be dried evenly, and a large number of small bubbles may appear in the swelling layer, affecting the overall appearance. In addition, the cross-linking is incomplete and the degree of cross-linking is insufficient, which may easily lead to the risk of dissolution and affect the service life of the tape. When drying, low temperatures at both ends and high temperatures in the middle are used for curing and drying, which can make the solvent in the tape evaporate and dry more evenly and reduce the appearance of bubbles in the swelling layer.
[0044] The coating speed of the first swelling layer is higher than that of the second swelling layer. On the one hand, this is because the viscosity of the raw material liquid of the first swelling layer is lower than that of the raw material liquid of the second swelling layer, making it easier to coat. On the other hand, the drying peak temperature of the first swelling layer is lower than that of the second swelling layer, and the first swelling layer is not completely dried. Therefore, the second swelling layer is wet-coated, and therefore also needs to be coated slowly to allow the two swelling layers to be better combined.
[0045] As a preferred technical solution, the porous polyimide substrate layer is prepared by the following method: 1) weighing 1-10 mmol of diamine and 10-30 ml of organic solvent, mixing the two, and rapidly stirring for 30-200 min, then dropping 1-10 mmol of dianhydride into the mixed solution, and continuing to stir for 5-20 h to obtain a light yellow transparent viscous polyamic acid dispersion with a solid content of 8 wt%-25 wt%;
[0046] 2) adding 1 to 5 g of sodium oxide particles having an average particle size of 1 to 10 μm after ball milling to the obtained polyamic acid dispersion, stirring evenly to obtain a mixed dispersion;
[0047] 3) coating the obtained mixed dispersion on a glass substrate, vacuum heating to 50-70°C and keeping the temperature for 1-5 hours, then heating with ventilation, keeping the temperature at 110-130°C for 1-2 hours and at 200-230°C for 1-2 hours, and then naturally cooling to room temperature;
[0048] 4) Soak the cooled glass substrate in hot water to remove the film, then put it into a water bath, boil it and keep it for 1-5 minutes, then soak it in 0.1-0.5M dilute hydrochloric acid for 10-30 minutes, take it out and rinse it with water, and treat it in a 100°C oven for 30 minutes to dry the water, and then obtain the porous polyimide substrate layer. The present invention utilizes sodium oxide particles in an organic solvent in a granular state. When the organic dispersion system evaporates to form a film, the sodium oxide particles will be evenly distributed in the polyimide film, and the sodium oxide will be dissolved and separated in the subsequent water boiling treatment, and the sodium oxide and the surface adsorbed alkali will be completely removed by soaking in hydrochloric acid. In addition, the sodium oxide of the present invention forms internal pores as a pore-forming agent, and forms sodium hydroxide when it contacts water, so that a high-concentration strong alkaline environment is formed in a short time in the local area, and the polyimide is partially dissolved, so that the pores are locally enlarged and the distribution is relatively more uniform; and when a large amount of water enters, the above-mentioned dissolution process will be inhibited, so that the internal pores are completely formed.
[0049] As a preferred technical solution, the dianhydride is pyromellitic dianhydride, the diamine is 4,4'-diaminodiphenyl ether, and the organic solvent is one or any combination of N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, and N,N-diethylacetamide.
[0050] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0051] A porous polyimide substrate obtained by a special method is used, and there are evenly distributed holes in the substrate. On the one hand, the contact surface is rougher, which is convenient for the contact and adhesion of the upper and lower layers, and the contact strength between the layers is improved. On the other hand, when the swelling layer on the substrate layer is formed, the pores of suitable size will make it easier for the first swelling layer raw material liquid with a certain viscosity to enter the pores. When the first swelling layer is solidified, it is in closer contact with the substrate, avoiding the swelling layer from separating from the substrate after swelling during battery use, and effectively reducing the possibility of the swelling tape breaking or generating internal defects. At the same time, compared with the first swelling layer raw material liquid, the second swelling layer raw material liquid has a higher viscosity, and a more uniform and dense film layer can be obtained when solidified into a film. When the second swelling layer contacts the electrolyte to swell, the formed swelling layer has a higher mechanical strength, and it can maintain mechanical stability for a longer time when in contact with the metal shell, so that the swelling layer fits the shell more closely and has better firmness. In addition, due to the high similarity of the material structure of the two swelling layers, the connection is tighter and not easy to delaminate. At the same time, the swelling tape structure is also convenient for the infiltration of the electrolyte, and the polyimide substrate can also maintain the required mechanical strength and maintain the overall structural stability of the swelling tape. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 It is a schematic structural diagram of the swelling tape of the present invention;
[0053] Among them, 1 is a swelling layer; 11 is a first swelling layer; 12 is a second swelling layer; 2 is a substrate layer; 21 is a hole; and 3 is a hot melt adhesive layer. DETAILED DESCRIPTION
[0054] In order to make the technical problems solved by the present invention, the technical solutions adopted and the technical effects achieved clearer, the technical solutions of the embodiments of the present invention are further described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0055] It should be noted that the reference to "embodiment" in this document means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of this phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0056] The experimental methods in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples are commercially available unless otherwise specified.
[0057] Attached Figure 1 The structural diagram of the swelling tape of the present invention is shown in FIG. Figure 1 It can be seen that the first swelling layer 11 is partially arranged in the holes of the substrate layer 2, and a small part of the hot melt adhesive layer 3 is arranged in the holes of the substrate layer 2. In the thickness direction of the substrate layer, there are some holes on the side of the hot melt adhesive layer 3 that are not filled with the swelling layer or the hot melt adhesive layer, which can serve as channels for the electrolyte, thereby improving the wetting performance of the electrolyte of the entire swelling tape. Example
[0058] First, a porous polyimide substrate layer is prepared, and the specific steps are as follows:
[0059] 1) Weigh 1 mmol of 4,4'-diaminodiphenyl ether and 10 ml of N,N-dimethylformamide, mix the two, and stir rapidly for 30 minutes. Then, add 1 mmol of pyromellitic anhydride dropwise to the mixed solution, and continue stirring for 5 hours to obtain a light yellow transparent viscous polyamic acid dispersion with a solid content of 8 wt%;
[0060] 2) adding 1 g of sodium oxide particles having an average particle size of 1 μm after ball milling to the obtained polyamic acid dispersion, stirring evenly to obtain a mixed dispersion;
[0061] 3) coating the obtained mixed dispersion on a glass substrate, vacuum heating to 50° C. and keeping the temperature for 1 hour, then heating with ventilation, keeping the temperature at 110° C. for 1 hour and at 200° C. for 1 hour respectively, and then naturally cooling to room temperature;
[0062] 4) Soak the cooled glass substrate in hot water to remove the film, then put it in a water bath, boil it and keep it for 1 minute, then soak it in 0.1M dilute hydrochloric acid for 10 minutes, take it out and rinse it with water, and treat it in an oven at 100°C for 30 minutes to dry the moisture, so as to obtain the porous polyimide substrate layer.
[0063] Then, the porous polyimide substrate layer prepared above is used as a substrate to prepare the swelling tape, and the specific steps are as follows:
[0064] (1) Preparation of the first swelling layer raw material solution:
[0065] (1.1) Weigh 20 parts by mass of polytrimethylene carbonate, 20 parts by mass of polypropylene glycol malonate, 1 part by mass of toluene diisocyanate, and 100 parts by mass of N,N-dimethylformamide; dissolve polytrimethylene carbonate and polypropylene glycol malonate in 80 parts by mass of N,N-dimethylformamide to obtain a solution 1;
[0066] (1.2) diluting toluene diisocyanate with 20 parts of N,N-dimethylformamide to obtain solution 2,
[0067] (1.3) adding the solution 2 to the solution 1, stirring evenly and filtering to obtain the first swelling layer raw material solution;
[0068] (2) Preparation of the second swelling layer raw material solution:
[0069] (2.1) Weigh 40 parts of polytrimethylene carbonate, 40 parts of polybutylene succinate, 5 parts of curing agent toluene diisocyanate, and 150 parts of N,N-dimethylformamide, and dissolve the polytrimethylene carbonate and polybutylene succinate in 120 parts of N,N-dimethylformamide to obtain solution 3;
[0070] (2.2) Dilute toluene diisocyanate with 30 parts of N,N-dimethylformamide to obtain solution 4,
[0071] (2.3) adding the solution 4 to the solution 3, stirring evenly and filtering to obtain the second swelling layer raw material solution;
[0072] (3) The first swelling layer raw material liquid is coated on the surface of the substrate layer 2 at a speed of 10 m / min, and enters the oven at this speed for curing and drying. The oven has 8 sections, and the temperatures of sections 1 to 8 are 90°C, 100°C, 110°C, 120°C, 130°C, 120°C, 110°C, and 90°C, respectively. After curing and drying, the first swelling layer 11 is obtained. Then, the second swelling layer raw material liquid is coated on the surface of the first swelling layer 11 away from the substrate layer 2 at a speed of 8 m / min, and enters the oven at this speed for curing and drying. The oven has 8 sections, and the temperatures of sections 1 to 8 are 90°C, 100°C, 115°C, 125°C, 140°C, 155°C, 110°C, and 90°C, respectively. After curing and drying, the second swelling layer 12 is obtained.
[0073] (4) applying the hot melt adhesive liquid onto the release surface of the release film, and obtaining a hot melt adhesive layer 3 after curing and drying;
[0074] (5) The surface of the base layer 2 stacked with the first swelling layer 11 and the second swelling layer 12 obtained in step (3) away from the first swelling layer 11 is attached to the surface of the hot melt adhesive layer 3 obtained in step (4) away from the release film and hot-pressed and laminated, and the swelling adhesive tape is obtained after removing the release film. Example
[0075] First, a porous polyimide substrate layer is prepared, and the specific steps are as follows:
[0076] 1) Weigh 10 mmol of 4,4'-diaminodiphenyl ether and 30 ml of N-methyl-2-pyrrolidone, mix the two, and rapidly stir for 200 min. Then, add 10 mmol of pyromellitic anhydride dropwise to the mixed solution, and continue stirring for 20 h to obtain a light yellow transparent viscous polyamic acid dispersion with a solid content of 15 wt%;
[0077] 2) adding 5 g of sodium oxide particles having an average particle size of 10 μm after ball milling to the obtained polyamic acid dispersion, stirring evenly to obtain a mixed dispersion;
[0078] 3) coating the obtained mixed dispersion on a glass substrate, vacuum heating to 70° C. and keeping the temperature for 5 h, then heating with ventilation, keeping the temperature at 130° C. for 2 h and at 230° C. for 2 h, respectively, and then naturally cooling to room temperature;
[0079] 4) Soak the cooled glass substrate in hot water to remove the film, then put it in a water bath, boil it and keep it for 5 minutes, then soak it in 0.5M dilute hydrochloric acid for 30 minutes, take it out and rinse it with water, and treat it in an oven at 100°C for 30 minutes to dry the moisture, so as to obtain the porous polyimide substrate layer.
[0080] Then, the porous polyimide substrate layer prepared above is used as a substrate to prepare the swelling tape, and the specific steps are as follows:
[0081] (1) Preparation of the first swelling layer raw material solution:
[0082] (1.1) Weigh 30 parts by mass of polytrimethylene carbonate, 30 parts by mass of polypropylene glycol malonate, 5 parts by mass of hexamethylene diisocyanate, and 150 parts by mass of ethyl acetate; dissolve polytrimethylene carbonate and polypropylene glycol malonate in 120 parts by mass of ethyl acetate to obtain a solution 1;
[0083] (1.2) diluting hexamethylene diisocyanate with 30 parts of ethyl acetate to obtain solution 2,
[0084] (1.3) adding the solution 2 to the solution 1, stirring evenly and filtering to obtain the first swelling layer raw material solution;
[0085] (2) Preparation of the second swelling layer raw material solution:
[0086] (2.1) Weigh 70 parts by mass of polytrimethylene carbonate, 70 parts of polybutylene succinate, 12 parts of curing agent hexamethylene diisocyanate, and 260 parts of ethyl acetate, and dissolve the polytrimethylene carbonate and polybutylene succinate in 208 parts of ethyl acetate to obtain a solution 3;
[0087] (2.2) diluting hexamethylene diisocyanate with 52 parts of ethyl acetate to obtain solution 4,
[0088] (2.3) adding the solution 4 to the solution 3, stirring evenly and filtering to obtain the second swelling layer raw material solution;
[0089] (3) The first swelling layer raw material liquid is coated on the surface of the substrate layer 2 at a speed of 12 m / min, and enters the oven at this speed for curing and drying. The oven has 8 sections, and the temperatures of sections 1 to 8 are 90°C, 100°C, 110°C, 120°C, 130°C, 120°C, 110°C, and 90°C, respectively. After curing and drying, the first swelling layer 11 is obtained. Then, the second swelling layer raw material liquid is coated on the surface of the first swelling layer 11 away from the substrate layer 2 at a speed of 10 m / min, and enters the oven at this speed for curing and drying. The oven has 8 sections, and the temperatures of sections 1 to 8 are 90°C, 100°C, 115°C, 125°C, 140°C, 155°C, 110°C, and 90°C, respectively. After curing and drying, the second swelling layer 12 is obtained.
[0090] (4) applying the hot melt adhesive liquid onto the release surface of the release film, and obtaining a hot melt adhesive layer 3 after curing and drying;
[0091] (5) The surface of the base layer 2 stacked with the first swelling layer 11 and the second swelling layer 12 obtained in step (3) away from the first swelling layer 11 is attached to the surface of the hot melt adhesive layer 3 obtained in step (4) away from the release film and hot-pressed and laminated, and the swelling adhesive tape is obtained after removing the release film. Example
[0092] First, a porous polyimide substrate layer is prepared, and the specific steps are as follows:
[0093] 1) Weigh 5 mmol of 4,4'-diaminodiphenyl ether and 20 ml of an organic solvent N,N-dimethylacetamide, mix the two, and rapidly stir for 100 min. Then, drop 5 mmol of pyromellitic dianhydride into the mixed solution, and continue stirring for 10 h to obtain a light yellow transparent viscous polyamic acid dispersion with a solid content of 15 wt%;
[0094] 2) adding 3 g of sodium oxide particles having an average particle size of 5 μm after ball milling to the obtained polyamic acid dispersion, stirring evenly to obtain a mixed dispersion;
[0095] 3) coating the obtained mixed dispersion on a glass substrate, heating to 50° C. in vacuum and keeping the temperature for 2 h, then heating by ventilation, keeping the temperature at 110° C. for 1 h and at 220° C. for 2 h, and then naturally cooling to room temperature;
[0096] 4) Soak the cooled glass substrate in hot water to remove the film, then put it in a water bath, boil it and keep it for 1.5 minutes, then soak it in 0.3M dilute hydrochloric acid for 20 minutes, take it out and rinse it with water, and treat it in an oven at 100°C for 30 minutes to dry the moisture, so as to obtain the porous polyimide substrate layer.
[0097] Then, the porous polyimide substrate layer prepared above is used as a substrate to prepare the swelling tape, and the specific steps are as follows:
[0098] (1) Preparation of the first swelling layer raw material solution:
[0099] (1.1) Weigh 30 parts of polytrimethylene carbonate, 30 parts of polypropylene malonate, 1 part of cyclic amine curing agent, 0.2 parts of p-toluenesulfonic acid catalyst, and 100 parts of N,N-dimethylformamide according to parts by mass; dissolve polytrimethylene carbonate and polypropylene malonate with 80 parts of N,N-dimethylformamide to obtain solution 1;
[0100] (1.2) dilute the curing agent and catalyst with 20 parts of N,N-dimethylformamide to obtain solution 2,
[0101] (1.3) adding the solution 2 to the solution 1, stirring evenly and filtering to obtain the first swelling layer raw material solution;
[0102] (2) Preparation of the second swelling layer raw material solution:
[0103] (2.1) Weigh 60 parts of polytrimethylene carbonate, 60 parts of polybutylene succinate, 8 parts of cyclic amine curing agent, 0.7 parts of p-toluenesulfonic acid catalyst, and 200 parts of N,N-dimethylformamide by weight, and dissolve polytrimethylene carbonate and polybutylene succinate with 160 parts of N,N-dimethylformamide to obtain solution 3;
[0104] (2.2) diluting the curing agent and catalyst with 40 parts of N,N-dimethylformamide to obtain solution 4,
[0105] (2.3) adding the solution 4 to the solution 3, stirring evenly and filtering to obtain the second swelling layer raw material solution;
[0106] (3) The first swelling layer raw material liquid is coated on the surface of the substrate layer 2 at a speed of 11 m / min, and enters the oven at this speed for curing and drying. The oven has 8 sections, and the temperatures of sections 1 to 8 are 90°C, 100°C, 110°C, 120°C, 130°C, 120°C, 110°C, and 90°C, respectively. After curing and drying, the first swelling layer 11 is obtained. Then, the second swelling layer raw material liquid is coated on the surface of the first swelling layer 11 away from the substrate layer 2 at a speed of 9 m / min, and enters the oven at this speed for curing and drying. The oven has 8 sections, and the temperatures of sections 1 to 8 are 90°C, 100°C, 115°C, 125°C, 140°C, 155°C, 110°C, and 90°C, respectively. After curing and drying, the second swelling layer 12 is obtained.
[0107] (4) applying the hot melt adhesive liquid onto the release surface of the release film, and obtaining a hot melt adhesive layer 3 after curing and drying;
[0108] (5) The surface of the base layer 2 stacked with the first swelling layer 11 and the second swelling layer 12 obtained in step (3) away from the first swelling layer 11 is attached to the surface of the hot melt adhesive layer 3 obtained in step (4) away from the release film and hot-pressed and laminated, and the swelling adhesive tape is obtained after removing the release film.
[0109] Comparative Example 1
[0110] First, a porous polyimide substrate layer is prepared, and the specific steps are as follows:
[0111] 1) Weigh 5 mmol of 4,4'-diaminodiphenyl ether and 20 ml of an organic solvent N,N-dimethylacetamide, mix the two, and rapidly stir for 100 min. Then, drop 5 mmol of pyromellitic dianhydride into the mixed solution, and continue stirring for 10 h to obtain a light yellow transparent viscous polyamic acid dispersion with a solid content of 15 wt%;
[0112] 2) adding 3 g of sodium oxide particles having an average particle size of 5 μm after ball milling to the obtained polyamic acid dispersion, stirring evenly to obtain a mixed dispersion;
[0113] 3) coating the obtained mixed dispersion on a glass substrate, heating to 50° C. in vacuum and keeping the temperature for 2 h, then heating by ventilation, keeping the temperature at 110° C. for 1 h and at 220° C. for 2 h, and then naturally cooling to room temperature;
[0114] 4) Soak the cooled glass substrate in hot water to remove the film, then put it in a water bath, boil it and keep it for 1.5 minutes, then soak it in 0.3M dilute hydrochloric acid for 20 minutes, take it out and rinse it with water, and treat it in an oven at 100°C for 30 minutes to dry the moisture, so as to obtain the porous polyimide substrate layer.
[0115] Then, the porous polyimide substrate layer prepared above is used as a substrate to prepare the swelling tape, and the specific steps are as follows:
[0116] (1) Preparation of swelling layer raw material liquid:
[0117] (1.1) Weigh 30 parts of polytrimethylene carbonate, 30 parts of polypropylene malonate, 1 part of cyclic amine curing agent, 0.2 parts of p-toluenesulfonic acid catalyst, and 100 parts of N,N-dimethylformamide according to parts by mass; dissolve polytrimethylene carbonate and polypropylene malonate with 80 parts of N,N-dimethylformamide to obtain solution 1;
[0118] (1.2) dilute the curing agent and catalyst with 20 parts of N,N-dimethylformamide to obtain solution 2,
[0119] (1.3) adding the solution 2 to the solution 1, stirring evenly and filtering to obtain a swelling layer raw material solution;
[0120] (2) coating the swelling layer raw material liquid onto the surface of the substrate layer 2 at a speed of 11 m / min, and entering the oven at this speed for curing and drying. The oven has 8 sections, and the temperatures of sections 1 to 8 are 90° C., 100° C., 110° C., 120° C., 130° C., 120° C., 110° C., and 90° C., respectively. After curing and drying, a swelling layer is obtained;
[0121] (3) applying the hot melt adhesive liquid onto the release surface of the release film, and obtaining a hot melt adhesive layer 3 after curing and drying;
[0122] (4) The surface of the base layer 2 laminated with the swelling layer obtained in step (3) away from the swelling layer is bonded and hot-pressed to the surface of the hot melt adhesive layer 3 obtained in step (3) away from the release film, and the swelling tape is obtained after removing the release film.
[0123] Comparative Example 2
[0124] The swelling tape is prepared with a purchased polyimide substrate. The polyimide has a porous structure, a porosity of 35%, and an average pore size of 0.5-5 μm. The specific steps for preparing the swelling tape are as follows:
[0125] (1) Preparation of the first swelling layer raw material solution:
[0126] (1.1) Weigh 30 parts of polytrimethylene carbonate, 30 parts of polypropylene malonate, 1 part of cyclic amine curing agent, 0.2 parts of p-toluenesulfonic acid catalyst, and 100 parts of N,N-dimethylformamide according to parts by mass; dissolve polytrimethylene carbonate and polypropylene malonate with 80 parts of N,N-dimethylformamide to obtain solution 1;
[0127] (1.2) dilute the curing agent and catalyst with 20 parts of N,N-dimethylformamide to obtain solution 2,
[0128] (1.3) adding the solution 2 to the solution 1, stirring evenly and filtering to obtain the first swelling layer raw material solution;
[0129] (2) Preparation of the second swelling layer raw material solution:
[0130] (2.1) Weigh 60 parts of polytrimethylene carbonate, 60 parts of polybutylene succinate, 8 parts of cyclic amine curing agent, 0.7 parts of p-toluenesulfonic acid catalyst, and 200 parts of N,N-dimethylformamide by weight, and dissolve polytrimethylene carbonate and polybutylene succinate with 160 parts of N,N-dimethylformamide to obtain solution 3;
[0131] (2.2) diluting the curing agent and catalyst with 40 parts of N,N-dimethylformamide to obtain solution 4,
[0132] (2.3) adding the solution 4 to the solution 3, stirring evenly and filtering to obtain the second swelling layer raw material solution;
[0133] (3) The first swelling layer raw material liquid is coated on the surface of the purchased polyimide substrate that has been corona treated in advance at a speed of 11 m / min, and enters the oven at this speed for curing and drying. The oven has 8 sections, and the temperatures of sections 1 to 8 are 90°C, 100°C, 110°C, 120°C, 130°C, 120°C, 110°C, and 90°C, respectively. After curing and drying, the first swelling layer 11 is obtained. Then, the second swelling layer raw material liquid is coated on the surface of the first swelling layer 11 away from the substrate layer 2 at a speed of 9 m / min, and enters the oven at this speed for curing and drying. The oven has 8 sections, and the temperatures of sections 1 to 8 are 90°C, 100°C, 115°C, 125°C, 140°C, 155°C, 110°C, and 90°C, respectively. After curing and drying, the second swelling layer 12 is obtained.
[0134] (4) applying the hot melt adhesive liquid onto the release surface of the release film, and obtaining a hot melt adhesive layer 3 after curing and drying;
[0135] (5) The surface of the base layer 2 stacked with the first swelling layer 11 and the second swelling layer 12 obtained in step (3) away from the first swelling layer 11 is attached to the surface of the hot melt adhesive layer 3 obtained in step (4) away from the release film and hot-pressed and laminated, and the swelling adhesive tape is obtained after removing the release film.
[0136] Comparative Example 3
[0137] First, a porous polyimide substrate layer is prepared, and the specific steps are as follows:
[0138] 1) Weigh 10 mmol of 4,4'-diaminodiphenyl ether and 8 ml of an organic solvent N,N-dimethylacetamide, mix the two, and rapidly stir for 100 min. Then, add 10 mmol of pyromellitic dianhydride dropwise to the mixed solution, and continue stirring for 10 h to obtain a polyamic acid dispersion;
[0139] 2) adding 6 g of sodium oxide particles to the obtained polyamic acid dispersion and stirring evenly to obtain a mixed dispersion;
[0140] 3) coating the obtained mixed dispersion on a glass substrate, heating to 50° C. in vacuum and keeping the temperature for 2 h, then heating by ventilation, keeping the temperature at 110° C. for 1 h and at 220° C. for 2 h, and then naturally cooling to room temperature;
[0141] 4) Soak the cooled glass substrate in hot water to remove the film, then put it in a water bath, boil it and keep it for 30 minutes, then soak it in 0.3M dilute hydrochloric acid for 20 minutes, take it out and rinse it with water, and treat it in an oven at 100°C for 30 minutes to dry the moisture, so as to obtain the porous polyimide substrate layer.
[0142] Then, the porous polyimide substrate layer prepared above is used as a substrate to prepare the swelling tape, and the specific steps are as follows:
[0143] (1) Preparation of the first swelling layer raw material solution:
[0144] (1.1) Weigh 30 parts of polytrimethylene carbonate, 30 parts of polypropylene glycol malonate, 1 part of cyclic amine curing agent, 0.2 parts of p-toluenesulfonic acid catalyst, and 100 parts of N,N-dimethylformamide in parts by mass; sequentially add polytrimethylene carbonate, polypropylene glycol malonate, cyclic amine curing agent, and p-toluenesulfonic acid into N,N-dimethylformamide to dissolve, stir evenly, and filter to obtain a first swelling layer raw material solution;
[0145] (2) Preparation of the second swelling layer raw material solution:
[0146] (2.1) Weigh 60 parts of polytrimethylene carbonate, 60 parts of polybutylene succinate, 8 parts of cyclic amine curing agent, 0.7 parts of p-toluenesulfonic acid catalyst, and 200 parts of N,N-dimethylformamide in parts by mass, add polytrimethylene carbonate, polypropylene malonate, cyclic amine curing agent, and p-toluenesulfonic acid to N,N-dimethylformamide in sequence to dissolve, stir evenly, and filter to obtain a second swelling layer raw material solution;
[0147] (3) The first swelling layer raw material liquid is coated on the surface of the substrate layer 2 at a speed of 15 m / min, and enters the oven at this speed for curing and drying. The oven has 8 sections, and the temperatures of sections 1 to 8 are 90°C, 100°C, 110°C, 120°C, 130°C, 120°C, 110°C, and 90°C, respectively. After curing and drying, the first swelling layer 11 is obtained. Then, the second swelling layer raw material liquid is coated on the surface of the first swelling layer 11 away from the substrate layer 2 at a speed of 7 m / min, and enters the oven at this speed for curing and drying. The oven has 8 sections, and the temperatures of sections 1 to 8 are 90°C, 100°C, 115°C, 125°C, 140°C, 155°C, 110°C, and 90°C, respectively. After curing and drying, the second swelling layer 12 is obtained.
[0148] (4) applying the hot melt adhesive liquid onto the release surface of the release film, and obtaining a hot melt adhesive layer 3 after curing and drying;
[0149] (5) The surface of the base layer 2 stacked with the first swelling layer 11 and the second swelling layer 12 obtained in step (3) away from the first swelling layer 11 is attached to the surface of the hot melt adhesive layer 3 obtained in step (4) away from the release film and hot-pressed and laminated, and the swelling adhesive tape is obtained after removing the release film.
[0150] Comparative Example 4
[0151] A porous polyimide substrate was prepared according to the method of Example 3, and the swollen tape was prepared using the substrate, with the specific steps of:
[0152] (1) Preparation of the first swelling layer raw material solution:
[0153] (1.1) Weigh 60 parts of polytrimethylene carbonate, 60 parts of polybutylene succinate, 8 parts of cyclic amine curing agent, 0.7 parts of p-toluenesulfonic acid catalyst, and 200 parts of N,N-dimethylformamide according to parts by mass, and dissolve polytrimethylene carbonate and polybutylene succinate with 160 parts of N,N-dimethylformamide to obtain solution 1;
[0154] (1.2) diluting the curing agent and catalyst with 40 parts of N,N-dimethylformamide to obtain solution 2,
[0155] (1.3) adding the solution 2 to the solution 1, stirring evenly and filtering to obtain the first swelling layer raw material solution;
[0156] (2) Preparation of the second swelling layer raw material solution:
[0157] (2.1) Weigh 30 parts of polytrimethylene carbonate, 30 parts of polypropylene glycol malonate, 1 part of cyclic amine curing agent, 0.2 parts of p-toluenesulfonic acid catalyst, and 100 parts of N,N-dimethylformamide according to mass parts; dissolve polytrimethylene carbonate and polypropylene glycol malonate with 80 parts of N,N-dimethylformamide to obtain solution 3;
[0158] (2.2) diluting the curing agent and catalyst with 20 parts of N,N-dimethylformamide to obtain solution 4,
[0159] (2.3) adding the solution 4 to the solution 3, stirring evenly and filtering to obtain the second swelling layer raw material solution;
[0160] (3) The first swelling layer raw material liquid is coated on the surface of the substrate layer 2 at a speed of 11 m / min, and enters the oven at this speed for curing and drying. The oven has 8 sections, and the temperatures of sections 1 to 8 are 90°C, 100°C, 110°C, 120°C, 130°C, 120°C, 110°C, and 90°C, respectively. After curing and drying, the first swelling layer 11 is obtained. Then, the second swelling layer raw material liquid is coated on the surface of the first swelling layer 11 away from the substrate layer 2 at a speed of 9 m / min, and enters the oven at this speed for curing and drying. The oven has 8 sections, and the temperatures of sections 1 to 8 are 90°C, 100°C, 115°C, 125°C, 140°C, 155°C, 110°C, and 90°C, respectively. After curing and drying, the second swelling layer 12 is obtained.
[0161] (4) applying the hot melt adhesive liquid onto the release surface of the release film, and obtaining a hot melt adhesive layer 3 after curing and drying;
[0162] (5) The surface of the base layer 2 stacked with the first swelling layer 11 and the second swelling layer 12 obtained in step (3) away from the first swelling layer 11 is attached to the surface of the hot melt adhesive layer 3 obtained in step (4) away from the release film and hot-pressed and laminated, and the swelling adhesive tape is obtained after removing the release film.
[0163] Comparative Example 5
[0164] The porous polyimide substrate layer was prepared mainly according to the method of Example 3, except that the average particle size of the sodium oxide after ball milling was 0.1-0.9 μm; the sodium oxide was kept for 1.5 min after boiling in a water bath, and was not soaked in acid, but was directly taken out and rinsed with water, and then treated in an oven at 100° C. for 30 min to dry the water, and then the porous polyimide substrate layer was used as a substrate to prepare a swelling tape according to the method of Example 3.
[0165] Performance Testing
[0166] Swelling degree and shape retention: The swollen tapes of Examples 1-3 and Comparative Examples 1-3 were cut into samples with a length of 50 mm×50 mm, and were placed in an electrolyte at 25° C. for swelling for 400 h and an electrolyte at 85° C. for swelling for 400 h, respectively, to test their swelling degree and observe their shape retention;
[0167] Specifically, the test method for swelling at 25°C is as follows: 1) refer to the GB / T7125-2014 standard to test the total thickness h0 of the sample; 2) cut the test sample into 50mm×50mm size and prepare 5 pieces; 3) put the cut tape into a PE bottle, pour the electrolyte to cover the sample, and swell in the electrolyte at 25°C for 400 hours; 4) After taking out the sample, flatten the sample, and use a 30cm steel ruler to test the length a and width b (in mm) of the sample, and refer to the GB / T7125-2014 standard to test the thickness h1 of the sample after immersion and baking in the electrolyte; 5) Swelling rate = a×b×h1 / (2500h0)×100%.
[0168] The test method for swelling at 85°C is the same as the test method for swelling at 25°C, except that the temperature in step 3) is changed to 85°C.
[0169] Adhesion of swelling layer after immersion for 400h : After soaking in electrolyte at 25℃ or 85℃ for 400h, the adhesion between the swelling layer and the substrate layer of the swelling tape is tested. The test method is: use a 200g pressing block with a bottom area of 50mm×50mm to press on the swelling layer, pull the pressing block at a speed of 10mm / s, and observe whether it falls off. It can be divided into the following forms:
[0170] No shedding: The swelling layer and the substrate layer have good adhesion, and there is no obvious change in appearance before the tensile force is applied;
[0171] Partial shedding: The adhesion between the swelling layer and the substrate layer is poor, and the swelling layer partially falls off;
[0172] Complete shedding: The swelling layer and the substrate layer fall off in one piece, and the swelling layer falls off almost completely.
[0173] The test results are shown in Table 1 below:
[0174] ,
[0175] As shown in Table 1, Examples 1-3 and Comparative Example 2 of the present invention have comparable swelling properties, but compared with Examples 1-3, the swelling layer of Comparative Example 2 partially falls off at 25°C and completely falls off when immersed in electrolyte at 85°C. This is mainly because the polyimide substrate layer used therein does not have a porous structure, so the swelling layer cannot be well combined with the substrate layer. The use of the swelling tape of Comparative Example 2 in lithium batteries will reduce the pass rate of the roller test and the like. Compared with Comparative Example 1, Examples 1-3 only have the first swelling layer in Comparative Example 1, which is thin and has a low viscosity of the raw material liquid, so it partially dissolves in the electrolyte. The use of the swelling tape of Comparative Example 1 in lithium batteries cannot achieve a good effect of filling the gaps. Compared with Example 3, in Example 1-3, the porous structure on the polyimide substrate layer in Example 3 is too small, and the proportion of the first swelling layer immersed in the polyimide substrate layer is low, so that part of the swelling layer falls off when immersed in the electrolyte, and the coating and drying speed of the first swelling layer is too fast, resulting in the surface of the first swelling layer being too wet when the second swelling layer is coated, and the two layers are not well combined, so the two swelling layers are separated and dissolved after being immersed in the electrolyte. In Example 4, the two swelling layers are arranged in reverse, so that the first swelling layer is less diffused and filled in the porous polyimide substrate, resulting in poor bonding between the swelling layer and the substrate. In addition, the outer swelling layer in the tape has poorer density than the inner swelling layer, and is more likely to swell, so that the mechanical strength of the entire swelling layer is reduced and the long-term stability is poor; in Example 5, the sodium oxide particles are small, so that the internal pores of the prepared polyimide are small. Although water washing has a certain pore expansion effect, the overall pore uniformity is poor, and the lack of acid washing also weakens the adhesion strength of the subsequent preparation of the swelling layer to a certain extent.
[0176] In summary, the two swelling layers prepared by the process of Examples 1-3 can be well combined and firmly fixed on the porous polyimide substrate, forming a swelling tape with stable performance.
[0177] The above is a detailed introduction to a swelling tape and its preparation method. The above content is a further detailed description of the present invention in combination with a specific preferred embodiment. It cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, without departing from the concept of the present invention, its structural form can be flexible and can derive a series of products. Just making a few simple deductions or substitutions should be regarded as belonging to the scope of patent protection of the present invention determined by the submitted claims.
Claims
1. A swelling tape comprising a swelling layer, a substrate layer and a hot melt adhesive layer stacked in sequence, characterized in that: The swelling layer is composed of two layers stacked together, wherein the first swelling layer is close to the substrate layer, and the second swelling layer is above the first swelling layer and away from the substrate layer; In parts by mass, the raw materials of the first swelling layer are: 20-30 parts of polytrimethylene carbonate; 20-30 parts of polypropylene malonate; 1-5 parts of curing agent; 0-1 parts of catalyst; 100-150 parts of solvent; In terms of parts by mass, the raw materials of the second swelling layer are: 40-70 parts of polytrimethylene carbonate; 40-70 parts of polybutylene succinate; 5-12 parts of curing agent; 0-1.5 parts of catalyst; 150-260 parts of solvent; The viscosity of the raw material liquid of the first swelling layer is less than the viscosity of the raw material liquid of the second swelling layer; The substrate layer is a porous polyimide substrate layer, which is prepared by the following method: 1) weighing 1-10 mmol of diamine and 10-30 ml of an organic solvent, mixing the two, and rapidly stirring for 30-200 min, then dropping 1-10 mmol of dianhydride into the mixed solution, and continuing to stir for 5-20 h to obtain a light yellow transparent viscous polyamic acid dispersion with a solid content of 8 wt%-25 wt%; 2) adding 1-5 g of sodium oxide particles with an average particle size of 1-10 μm after ball milling to the obtained polyamic acid dispersion, stirring evenly to obtain a mixed dispersion; 3) applying the obtained mixed dispersion on a glass substrate, vacuum heating to 50-70° C. and keeping it warm for 1-5 hours, then heating with ventilation, keeping it warm at 110-130° C. for 1-2 hours and at 200-230° C. for 1-2 hours, respectively, and then naturally cooling it to room temperature; 4) soaking the cooled glass substrate in hot water to remove the film, then putting it in a water bath, boiling it and keeping it for 1-5 minutes, then soaking it in 0.1-0.5 M dilute hydrochloric acid for 10-30 minutes, taking it out and rinsing it with water, treating it in a 100° C. oven for 30 minutes to dry the moisture, and then obtaining the porous polyimide substrate layer; The first swelling layer is at least partially disposed in the pores of the substrate layer.
2. The swelling tape according to claim 1, characterized in that 30% to 50% of the first swelling layer is disposed in the pores of the substrate layer.
3. The swelling tape according to claim 2, characterized in that The thickness of the first swelling layer located on the surface of the substrate layer is 1-2 μm; the thickness of the second swelling layer is 2-4 μm.
4. The swelling tape according to claim 1, characterized in that: The thickness of the porous polyimide substrate layer is 10-20 μm.
5. The swelling tape according to claim 1, characterized in that: The porous polyimide substrate layer has a porosity of 40-80%, and the pores in the substrate are randomly distributed and do not penetrate the substrate from top to bottom.
6. A method for preparing the swelling tape according to claim 1, characterized in that: The steps include: (1) Preparation of the first swelling layer raw material solution: (1.1) Weighing polytrimethylene carbonate, polypropylene glycol malonate, a curing agent, an optional catalyst and a solvent according to the mass parts of the raw materials for the first swelling adhesive layer, and dissolving polytrimethylene carbonate and polypropylene glycol malonate with 4 / 5 of the solvent to obtain a solution 1; (1.2) diluting the curing agent and the optional catalyst with 1 / 5 of the amount of solvent to obtain solution 2, (1.3) adding the solution 2 to the solution 1, stirring evenly and filtering to obtain the first swelling layer raw material solution; (2) Preparation of the second swelling layer raw material solution: (2.1) Weighing polytrimethylene carbonate, polybutylene succinate, a curing agent, an optional catalyst and a solvent according to the mass fraction of the raw materials for the second swelling adhesive layer, and dissolving polytrimethylene carbonate and polybutylene succinate with 4 / 5 of the solvent to obtain a solution 3; (2.2) diluting the curing agent and the optional catalyst with 1 / 5 of the amount of solvent to obtain solution 4, (2.3) adding the solution 4 to the solution 3, stirring evenly and filtering to obtain the second swelling layer raw material solution; (3) applying the first swelling layer raw material liquid to the surface of the substrate layer, and obtaining the first swelling layer after curing and drying, and then applying the second swelling layer raw material liquid to the surface of the first swelling layer away from the substrate layer, and obtaining the second swelling layer after curing and drying; (4) applying the hot melt adhesive liquid onto the release surface of the release film, and obtaining a hot melt adhesive layer after curing and drying; (5) The surface of the substrate layer stacked with the first swelling layer and the second swelling layer obtained in step (3) away from the first swelling layer is attached to the surface of the hot melt adhesive layer obtained in step (4) away from the release film and hot-pressed and laminated, and the swelling tape is obtained after removing the release film.
7. The method for preparing a swelling tape according to claim 6, characterized in that: The porous polyimide substrate layer is prepared by the following method: 1) weighing 1-10 mmol of diamine and 10-30 ml of organic solvent, mixing the two, and rapidly stirring for 30-200 min, then dropping 1-10 mmol of dianhydride into the mixed solution, and continuing to stir for 5-20 h to obtain a light yellow transparent viscous polyamic acid dispersion with a solid content of 8 wt%-25 wt%; 2) adding 1 to 5 g of sodium oxide particles having an average particle size of 1 to 10 μm after ball milling to the obtained polyamic acid dispersion, stirring evenly to obtain a mixed dispersion; 3) coating the obtained mixed dispersion on a glass substrate, vacuum heating to 50-70°C and keeping the temperature for 1-5 hours, then heating with ventilation, keeping the temperature at 110-130°C for 1-2 hours and at 200-230°C for 1-2 hours, and then naturally cooling to room temperature; 4) Soak the cooled glass substrate in hot water to remove the film, then put it in a water bath, boil it and keep it for 1-5 minutes, then soak it in 0.1-0.5M dilute hydrochloric acid for 10-30 minutes, take it out and rinse it with water, and treat it in an oven at 100°C for 30 minutes to dry the moisture, so as to obtain the porous polyimide substrate layer.
8. The method for preparing a swelling tape according to claim 7, characterized in that: The dianhydride is pyromellitic dianhydride, the diamine is 4,4'-diaminodiphenyl ether, and the organic solvent is one or any combination of N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, and N,N-diethylacetamide.
Citation Information
Patent Citations
Swelling tape for filling gap
CN104798223A
Special thickness swelling adhesive tape for cylindrical battery and preparation method thereof
CN113072889A
Electrode assembly for lithium ion, lithium ion secondary battery assembly using the same
CN1992393B
Electrode plate, battery cell and lithium ion battery
CN219123264U
Swelling adhesive tape and battery
CN220283958U